Implementation Of The Independent Curriculum In Mathematics Learning For Class X Vocational School In The Administrative City Of East Jakarta - Asmarawati, Endah (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this study is to describe: (1) how the teachers prepared mathematics learning activities in an independent curriculum, (2) how teachers implement an independent curriculum in mathematics learning, (3) the obstacles experienced by teachers in implementing an independent curriculum in mathematics learning. Qualitative research was aapplied in this research. The subject of the research were mathematics teacher of class X SMK in East Jakarta Administrative City. The subjects are selected based on teachers who frequently attended training and independent curriculum webinars and suggestions from the principal. The data collection techniques was done by observation, interviews and documentation. Data validity uses source triangulation. The data analysis technique used Miles and Huberman’s concept that are data collection, data reduction, presentation of data and drawing conclusions. The results of the study can be stated as follows: (1) How to organize independent curriculum implementation activities in mathematics learning is done by: (a) preparing Education Operational Unit Curriculum (KSOP) documents, education calendars, annual programs, semester programs to determine effective weeks, (b) preparing learning outcomes (CP), goals learning (TP), learning objectives flow (ATP), student worksheets (LKPD) and appropriate learning methods, (c) compiling teaching modules and their assessments and preparing Pancasila student profile projects. (2) The process of implementing an independent curriculum in mathematics learning carried out by teachers is in accordance with the lesson plan. Teachers use active learning strategies and learning models to make students active in learning activities and teachers only as facilitators. In learning the teacher also carries out several activities to strengthen the profile of Pancasila students to students in order to achieve learning objectives. (3) The obstacles experienced by teachers in implementing an independent curriculum in mathematics learning include: (a) students still have difficulty adapting to offline learning, (b) students' basic knowledge of mathematics is low and students tend to be passive even though they have been given a stimulus by the teacher.